Analysis of the Impact of Success Indicators Spread on Social Media on the Mental Health of Generation Z - Ramadhan, Wisnu; Karnita, Rosa (PT Ininnawa Paramacitra Edukasi, 2025)
Social media has become inseparable from every young person's life in today's digital age, especially in Generation Z. However, overexposure to standards of achievement characterized by success indicators displayed on various social media platforms can harm young people's mental and emotional health. Indicators of success on social media often create feelings of anxiety, low self-esteem, and social anxiety, especially with comparisons to others' achievements on social media that seem idealized and unattainable and worry about the future. This study aims to identify the adverse effects of social media success indicators on young people's mental health and provide a deeper understanding of the impact of these issues. The methods used in this study were questionnaires, netnographic observations, and a literature review focusing on the social media exposure of Generation Z, aged 18 - 24. The data collected revealed the behavioral patterns and perceptions of Generation Z towards expectations on social media. In addition, the results of this study can be recommended to find practical steps so that Generation Z is not easily influenced by indicators of success and achievement of others only seen on social media. By providing a perspective on the use of social media, this research seeks to help Generation Z develop their inner talents and not get hung up on the often unrealistic standards of achievement in life through educational campaigns on social media.